A citywide, clonal outbreak of Pseudomonas aeruginosa during a drought - Opperman, Christoffel Johannes (Department of Clinical Laboratory Sciences, 2022)
Background Outbreaks of community-acquired Pseudomonas aeruginosa are typically small and localized. We investigated an increase in P. aeruginosa clinical isolates in Cape Town, South Africa during a severe drought. Methods Cases were defined as P. aeruginosa isolated from any clinical sample, and “wild-type” as susceptibility to all antibiotics tested. Residential addresses of community-acquired wild-type cases were mapped. Whole genome sequencing and multi-locus sequence typing were used to determine clonality and identify virulence genes. A modified case-control study in a subset of patients with bloodstream infection compared demographic and clinical characteristics between sequence types. Results The outbreak lasted 10 months from December, 2016 to September, 2017 with 3,321 documented cases. At the peak, cases reached 2.3-fold baseline and the city's dams reached a nadir of 19% capacity. Cases were distributed widely across the city. Multi-locus sequence type (ST) 303 was found in 27 of 42 (64%) blood culture isolates of P. aeruginosa during the outbreak, one of 19 (5%) before, and none of 11 after. ST303 infection was independently associated with younger age, but not with co-morbidities nor increased mortality. Fifty-one virulence genes were differentially present in ST303 compared with other sequence types, including genes involved in biofilm formation, iron uptake, and gut penetration. Conclusion The investigation confirmed a citywide outbreak of P. aeruginosa coinciding with and potentially related to a severe drought. We identified a predominant outbreak-associated clone, ST303, which harboured genes that could contribute to virulence and survival in drought-related conditions. Enhanced surveillance for P. aeruginosa during periods of drought is recommended.